2022-RA-1623-ESGO Effect of bevacizumab and complete cytoreductive surgery in advanced low grade serous ovarian cancer: a secondary analysis of MITO 22. (20th October 2022) - Musacchio, Lucia; Turinetto, Margherita; Bartoletti, Michele; Arenare, Laura; Califano, Daniela; Tuninetti, Valentina; Cormio, Gennaro; Pisano, Carmela; Valabrega, Giorgio; Marchetti, Claudia; Cecere, Sabrina Chiara; Greggi, Stefano; et al.
Abstract : Introduction/Background: The aim of the present analysis was to explore the efficacy of Bevacizumab (Bev) on survival outcome in advanced low grade serous ovarian cancer (LGSOC) both in first line and in recurrent setting. Methodology: In this multicenter retrospective case control study, we compared LGSOC patients treated with chemotherapy (CT) with or without Bev, enrolled in MITO22 study. Patients receiving Bev in first-line or recurrence were considered and matched with patients receiving only CT (stage III and IV in first line; platinum based-CT in second line). Descriptive and survival analyses were performed for each group. Furthermore, the effect of upfront complete cytoreduction on progression free survival (PFS) was assessed. Results: Out of 128 patients included in MITO 22, 46 LGSOC patients receiving Bev in first-line setting or at the time of first recurrence were identified.In first line, 30 patients received Bev+CT and 65 CT alone. Median PFS were 47.86 months (95% CI: 31.48 -NR) and 22.63 months (95% CI 15 -39.24), respectively. This data was statistically significant at univariate analysis while it wasn't at the multivariate analyses where RT was considered. Median PFS was not reached (95% CI 31.5-not reached) in patients achieving complete cytoreduction and receiving Bev, while it was 32.4 months (95% CI: 7.9–37.4) in patients with RT.In the recurrent setting, 16 patients received Bev+CT and 33 women platinum-based CT alone at the time of relapse.PFS were 37.1 months (95 CI: 13.42–40.56) and 11.22 months (95% CI: 8.26–15.63), respectively, being statistically significant (p value 0.013); no multivariate analysis were performed due to the low number of patients receiving secondary cytoreduction. Conclusion: Our study suggests that Bev might be effective in LGSOC both at diagnosis and at the time of relapse. The role of optimal cytoreduction is also confirmed. This data warrants further studies.